Job Burnout of Generation Y Professional Nurses at a Government Hospital - Kakandee, Nisakorn; Cheevakasemsook, Aree; Triwichitkhun, Duangkamol (Journal of The Royal Thai Army Nurses, 2020)
The purposes of this mixed-methods research were: 1) to investigate job burnout and its related factors of generation Y professional nurses at a government hospital, 2) to compare job burnout among classified by departments, and 3) to explore a guideline for their job burnout management. The samples comprised 2 groups: 1) 112 nurses who answered questionnaires and were selected by systematic random sampling, and 2) fourteen nurses who attended focus group discussion and were selected by purposive sampling. Research tools which were done for content validity with 0.8-1.0 included: 1) a job burnout questionnaire and 2) A question guideline for focus group discussion with reliability 0.94. Research data were analyzed by frequency, percentage, mean, standard deviation, and content analysis. The results showed. 1) Generation Y professional nurses rated their job burnout overall at the low level. With itemized scores, emotional exhaustion dimension was at the moderate level; while, depersonalization and decreased occupational accomplishment dimensions were at the low level. 2) Professional nurses of special unit groups and the Inpatient unit significantly rated their burnout higher than the Outpatient department at the level .05. 3) Related factors included work overload, staff nurse shortage, working beyond the standard criteria, head nurses’ lack of understanding staff, difficulty of exchanging shifts, insufficient equipment. Finally, 4) The guideline for their burnout management comprised documentation workload reduction, providing sufficient nursing staffing, setting job priority, working quicker, increasing communication channels with supervisors, adequate supply management, additional remuneration for personnel with more workload, good relationship, and positive thinking.